NOVEL SNP OF CALPAIN-1 (CAPN1) GENE AND ITS ASSOCIATION WITH CARCASS AND MEAT CHARACTERISTICS TRAITS IN BALI CATTLE - Pratiwi, N.; Maskur, M.; Priyanto, R.; Jakaria, J. (Diponegoro University, 2016)
Calpain-1 gene (CAPN1) produces an calpain enzyme controlling structure of meat protein and tenderness. The aims of this study were to identify Single Nucleotide Polymorphism (SNP) in exon 5 and 6 of CAPN1 gene and its associate with carcass and meat characteristic traits in bali cattle. A total of 48 bali cattles from BPTU-HMT Bali Cattle, Bali Province were used in the research. SNP in exon 5 and 6 of CAPN1 gene were identify with direct sequencing using MEGA 5 program. Analysis of polymorphism was conducted by PopGen 1.32 software to identify frequencies of genotype, allele and Hardy-Weinberg equilibrium. The association of CAPN1 gene genotype with carcass and meat characteristic traits was analyzed using Generalized Linear Model (GLM) procedure of SAS. Sequencing analysis at exon 5-6 of CAPN1 gene in Bali cattle resulted in eight polymorphic SNPs. They are c.3669T>C, c.3854G>A, c.3881T>C, c.3899C>T, c.3908C>G, c.4002C>A, c.4021G>T and c.4037A>C. The SNPs c.3669T>C, c.3854G>A and c.3899C>T were significantly (P<0.05) associated with rump thickness (RT), rump fat thickness (RFT) and marbling score (MS), while SNP c.4037A>C was not significantly associated with carcass and meat characteristic traits. The SNPs were significantly associated with carcass and meat characteristic traits namely c.3669T>C, c.3854G>A and c.3899C>T. Those SNPs may be used as candidate marker for Marker Assisted Selection (MAS) in bali cattle.